Series del Manejo de Vegetales en Florida – Tipos de Tomate Roma y Redondo - Steven A. Sargent; Jeffrey K. Brecht; Teresa Olczyk; Elena Lon Kan (EDIS)
Revised! HS1073, an 11-page illustrated fact sheet by Steven A. Sargent, Jeffrey K. Brecht, Teresa Olczyk and Elena Lon Kan, focuses on effective techniques for post-harvest handling of Roma and round tomatoes. Includes references. Published by the UF Department of Horticultural Sciences, November 2006.